2008
DOI: 10.1136/ard.2008.092767
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab for long-term treatment of psoriatic arthritis: 2-year data from the Adalimumab Effectiveness in Psoriatic Arthritis Trial (ADEPT)

Abstract: Objective:To evaluate the long-term effectiveness and tolerability of adalimumab in the treatment of psoriatic arthritis (PsA).Methods:Patients with PsA who completed a 24-week, double-blind study of adalimumab versus placebo were eligible to enroll in an open-label extension study and receive adalimumab 40 mg subcutaneously every other week for up to an additional 120 weeks. At the time of this analysis, available efficacy evaluations throughout 2 years of treatment (n  =  245) included American College of Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
191
0
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(210 citation statements)
references
References 22 publications
9
191
0
10
Order By: Relevance
“…After nearly 3 years of follow-up, the most common AE in the adalimumab trial in PsA patients were similar to those in the first 6 months of the study: upper respiratory tract infections, nasopharyngitis, and sinusitis were seen in 21.5, 17.4, and 10.7 %, respectively [8]. Similar AE were seen in AS patients in the ATLAS trial over a period of 2 years [9].…”
Section: Infectionssupporting
confidence: 59%
See 2 more Smart Citations
“…After nearly 3 years of follow-up, the most common AE in the adalimumab trial in PsA patients were similar to those in the first 6 months of the study: upper respiratory tract infections, nasopharyngitis, and sinusitis were seen in 21.5, 17.4, and 10.7 %, respectively [8]. Similar AE were seen in AS patients in the ATLAS trial over a period of 2 years [9].…”
Section: Infectionssupporting
confidence: 59%
“…Transient elevation of liver enzymes was seen with adalimumab [8], certolizumab [22], and golimumab [23]. Similarly, in the golimumab study of PsA patients, Kavanaugh et al noted hyperbilirubinemia in study patients [24].…”
Section: Laboratory Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While traditional disease-modifying antirheumatic drugs (DMARD) such as methotrexate appear to offer limited protection from ongoing joint damage in PsA 15 , a newer group of biologic agents, the tumor necrosis factor (TNF) inhibitors, can halt radiographic progression over a period of weeks to years 16,17,18,19 . There are currently 4 TNF inhibitors available to Canadian physicians for treating PsA: etanercept 17,19,20,21,22,23 , infliximab 18,24 , adalimumab 16,25,26 , and golimumab 27 .…”
Section: Rheumatologymentioning
confidence: 99%
“…Nonbiologic disease-modifying antirheumatic drugs (DMARDs), methotrexate (MTX) in particular, are the first-choice treatment of PsA, despite disappointing efficacy in clinical trials (7). Recent studies have demonstrated that tumor necrosis factor (TNF) inhibitors are efficacious against both the psoriatic and the arthritic components of PsA (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%